KOMPONEN AKTIF DUA PULUH JENIS TUMBUHAN OBAT DI TAMAN NASIONAL GUNUNG HALIMUN - Zulnely Zulnely; E S Sumadiwangsa; Erik Dahlian; Umi Kulsum (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
The forest in Gunung Halimun National Park belonged to the Indonesian tropical forests, is rich in medicinal plant species. An experiment was conducted to identify active ingredients in 20 plant species collected from the region. Results of bio-testing using Brine Shrimp's methods revealed that 11 species showed medicinal efficacy as indicated by the toxicity. Further analysis revealed that 11 plant species contained a toxic cheminal categorized as saponine. Meanwhile, 10 plant species contained other active ingradients categorized as flavonoid, steroid and tanin, 7 species contained triterpenoids and 2 species contained alkaloids.